2009
DOI: 10.1152/ajpheart.00882.2008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mitral regurgitation on left ventricular anatomic and molecular remodeling and systolic function: implication for outcome

Abstract: The aim of the study was to assess the impact of mitral regurgitation (MR) on left ventricular (LV) anatomic and molecular remodeling and function and to determine whether early LV remodeling and function predict long-term outcome in experimental organic MR. A new rodent model of chronic MR was created. Twenty-eight rats had surgically induced MR, twelve rats had a sham operation, and twelve rats had no operation. LV diameters, volume, and mass and LV ejection fraction (LVEF) and LV fractional shortening (LVFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…MR was induced using techniques which were previously described. 16 An intracardiac echocardiographic catheter (Acuson/Siemens Corporation, Mountain View, CA) was used to obtain transesophageal echocardiographic images to assess the severity of MR.…”
Section: Rat Model Of Mrmentioning
confidence: 99%
See 2 more Smart Citations
“…MR was induced using techniques which were previously described. 16 An intracardiac echocardiographic catheter (Acuson/Siemens Corporation, Mountain View, CA) was used to obtain transesophageal echocardiographic images to assess the severity of MR.…”
Section: Rat Model Of Mrmentioning
confidence: 99%
“…MR was induced using techniques which were previously described. 16 An intracardiac echocardiographic catheter (Acuson/Siemens Corporation, Mountain View, CA) was used to obtain transesophageal echocardiographic images to assess the severity of MR. 17 MR was considered significant if a regurgitant jet area occupied >40% of left atrial area with a visible MR vena contracta or a reversed pulmonary venous flow pattern.…”
Section: Rat Model Of Mrmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of other studies were conflicting, probably because of small number of patients collected and different reperfusion strategies [21]. Experimental studies showed direct influence of MR on remodeling and on extracellular matrix growth [22]. Amigoni et al [23] in 496 patients with left ventricular dysfunction during acute MI, demonstrated correlation between the grade of MR and end-diastolic or end-systolic left ventricular volumes, increased sphericity index and decreased LVEF at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that patients with chronic MR may stay asymptomatic for a long time and regarding the reversibility of disease progress and contractile reserve after cardiac surgery we wanted to objectify this impact on 3 different groups of patients with different mitral valve disease [10].…”
Section: Muscle Preparationmentioning
confidence: 99%